Emotional factors and self-efficacy in the psychological well-being of trainee teachers - Gilar-Corbi, Raquel; Perez-Soto, Natalia; Izquierdo, Andrea; Castejón, Juan-Luis; Pozo-Rico, Teresa (Frontiers in Psychology, 2024)
The relationship among emotional intelligence, stress, and self-efficacy is a crucial factor in shaping psychological well-being. It has a significant impact on important areas such as health, academic and professional performance, and overall quality of life. Using a hierarchical approach, this study aimed to identify, the specific predictors of psychological well-being, including emotional intelligence, stress, resilience, burnout, and self-efficacy, among higher education students pursuing a bachelor's degree in education. We also examined gender differences amongst these predictors. This study involved 338 higher education students pursuing a primary education teaching degree. The results obtained using the hierarchical regression analysis technique, indicated that the resilience measure, the burnout measure, and the factor of the teacher self-efficacy measure related to self-efficacy in coping with challenges and effectiveness in dealing with change in the educational context, significantly contributed to explaining psychological well-being in the total sample. Furthermore, the predictors of psychological well-being differed between male and female samples. Finally, these findings are discussed in terms of their theoretical and practical implications for improving the training process of future teachers.